Study of the Inhibitory Effect of the Ethanolic Extract of a Number of Local Medicinal Plants on the Growth of Proteus spp. in vitro: Jinan Abdul-Amir Sabeeh and Zainab Adnan Hatem - Sabeeh, Jinan Abdul-Amir; Hatem, Zainab Adnan (The Iraqi Journal of Veterinary Medicine, 2022)
The present study was designed to evaluate the inhibitory effect of six local medicinal plant ethanolic extracts (Quercus robur, Vitis vinifera, Cinnamomum zeylanicum, Ginger officinale, Thymus vulgaris, and Coriandrum sativum) on the growth of Proteus spp. in vitro. For this purpose, graduate concentrates for each extract (50, 100, 200, and 400 mg/mL) were prepared and tested. The result showed that all the studied medicinal plants have antibacterial activity against Proteus spp., with the exception of Coriandrum sativum, which did not show any inhibitory activity against the growth of the studied bacteria in vitro. And the more active plant in inhibiting the growth of the studied bacteria was Quercus robur, followed by Vitis vinifera, Cinnamomum zeylanicum, Ginger officinale, and Thymus vulgaris. Also, there were no significant differences between the effects of the different concentrations of Thymus vulgaris and Coriandrum sativum, while there were significant differences between the effects of Cinnamomum zeylanicum concentrations and the concentrations of 400 and 200 mg/mL of Ginger officinale compared with 100 and 50 mg/mL of Quercus robur, while the ethanolic extract of Vitis vinifera showed a significant difference between the effects of the 400 mg/mL with the other studied concentrations.